Training Future Teachers of Mathematics and Computer Science: Experience, Problems, and Prospects - Olga Yu. Glukhova; Nina A. Rusakova (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки, 2025)
Engineering, digital technologies, and fundamental sciences are experiencing personnel shortage. Profound mathematical education is the basis of fundamental and applied research. However, university applicants have recently been demonstrating poor results in Mathematics, probably, as a result of understaffing in schools. Schools need teachers of Mathematics and Computer Science with fundamental knowledge of the subject, advanced teaching methodology, and professional pedagogical competencies. The author examined the experience of teachers’ training at classical universities to profile a modern school teacher. Future teachers of Mathematics and Computer Science should not have to major in pedagogy: a block of pedagogical and methodical disciplines can be integrated into various curricula to provide university graduates with a teaching qualification. The article introduces some case studies and recommendations on how to improve teachers’ training in mathematics and computer science in the Kemerovo Region (Kuzbass).